A clinical study on prevalence of subclinical hypothyroidism in patients with cholelithiasis in a tertiary care center in South India - A., Khalilur Rahman; S., Rajesh; Balineni, Pradeep (International Surgery Journal, 2021)
Background: Gall stones are the most common biliary pathology. Hypothyroidism has been shown to promote gall stone formation and prevalence of clinical hypothyroidism in patients with cholelithiasis is extensively studied. This study aimed to find the prevalence of subclinical hypothyroidism in patients with cholelithiasis. Methods: A prospective study on 94 patients was carried in Saveetha medical college and hospital, Tamil Nadu, India between March 2017 and June 2019. All patients underwent imaging studies for confirmation of gall stone disease and serum FT3, FT4 and TSH estimation done. Results: Out of 94 patients, 47 patients were between 30-50 years (50%). 30 (31.9%) patients were hypothyroid and 64 (68.1%) were euthyroid. Among the hypothyroid patients, 3 (3.2%) had clinical hypothyroidism and 27 (28.7%) had subclinical hypothyroidism. 80 (85.1%) patients had multiple calculi and 14 (14.9%) of patients had single calculus. Conclusions: Majority of patients were in the age group of 30-50 years with females 53.2% and males 46.8%. Hypothyroidism was diagnosed in nearly one-third of patients in our study with a high prevalence of subclinical hypothyroidism (28.7%). No significant correlation was found with respect to age, gender, number of gall stones to serum TSH levels.